Molecular Targets Related Drug Resistance Mechanisms in MDR-, XDR-, and TDR-Mycobacterium tuberculosis Strains - Hameed, H. M. Adnan; Islam, Md Mahmudul; Chhotaray, Chiranjibi; Wang, Changwei; Liu, Yang; Tan, Yaoju; Li, Xinjie; Tan, Shouyong; Delorme, Vincent; Yew, Wing W.; Liu, Jianxiong; Zhang, Tianyu (Frontiers in Cellular and Infection Microbiology, 2018)
Tuberculosis (TB) is a formidable infectious disease that remains a major cause of death worldwide today. Escalating application of genomic techniques has expedited the identification of increasing number of mutations associated with drug resistance in Mycobacterium tuberculosis. Unfortunately the prevalence of bacillary resistance becomes alarming in many parts of the world, with the daunting scenarios of multidrug-resistant tuberculosis (MDR-TB), extensively drug-resistant tuberculosis (XDR-TB) and total drug-resistant tuberculosis (TDR-TB), due to number of resistance pathways, alongside some apparently obscure ones. Recent advances in the understanding of the molecular/ genetic basis of drug targets and drug resistance mechanisms have been steadily made. Intriguing findings through whole genome sequencing and other molecular approaches facilitate the further understanding of biology and pathology of M. tuberculosis for the development of new therapeutics to meet the immense challenge of global health.